A Content Analysis of DD News Show: - Good News India: Examining the content and audience reception of DD News Show: Good News India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Good News is the selective version of world positive events and happenings that we read daily in Newspaper, Television, Radio and Internet. Good News is the stories related to health, positivity, leisure, happiness, achievements, and victory. In the present scenario people start their day with negative stories that published on newspaper front page and watch on television breaking events, and listen breaking news on radio.Now there are news applications available on internet that is full of negative and useless stories. But if we take a positive side there is national news channel of India DD news that provides us sensible, soft stories. We are mostly satisfied with the content of DD News (Only news, complete news).The study was conducted for examining the content of DD News Show, Good News India. We analyzed the content of five episodes of Good News India show. It also investigated how this content is useful for the audience who are watching this show every week. We also analyzed the comments of audience that are available on you tube related to this show. We analyzed the content of the episodes dated- 20-11-2016, 23-02-17, 19-3-2017, 2-04-2017, and 9-04-2017.